Desain Dan Analisis Kekuatan Struktur Kontruksi Kapal Patroli 13 Meter Menggunakan Finite Element Method (FEM) - Rahmat Rosid; Mardi Santoso; Benedicta Dian Alfanda (Proceedings Conference on Marine Engineering and its Application, 2023)
In the process of maintaining security and maintenance of the approach lightingsystem (ALS) at the airport area in Natuna which was built on the Natuna coast. So weneed a patrol boat that can meet the criteria in terms of the strength of the ship's structureto maneuver properly and accept internal and external loads. Structural capabilities thatare sufficiently safe are permitted according to BKI rules for ships made of fiberglassreinforced plastic. Case of slamming loading, it will be analyzed whether it is sufficientlysafe in terms of the strength of the construction structure on the 13-meter patrol boat thatloading may occur due to ship operations in the area around the airport. The initialcalculation is to calculate the scantling with a scantling weight of 2,226 tons and then drawthe construction in accordance with the lines plan and general arrangement of the 13 meterpatrol boat. Followed by the provision of a static load from slamming loading of 15,237KPa when the ship is at full speed of 20 knots to find out the response from the ship'sconstruction made of FRP. The value analyzed is the maximum stress (von mises) using theFinite Element Method (FEM) with static structural analysis and slamming loading in theform of pressure on the software as the method chosen in this study. Then raises the stressvalue in the ANSYS software, the maximum stress value that occurs in the construction is13.808 MPa and from this maximum stress value the safety factor value can be calculatedto find out how safe the ship's construction is if it is given a slamming load on the ship. Thesafety factor value in this study is 7,097. From the value of the safety factor it is knownthat the ship is still able to accept slamming loads at full speed.